Analisis Pengaruh Budaya Organisasi Dan Pengalaman Kerja Terhadap Kinerja Pegawai Badan Pengelola Keuangan Dan Pendapatan Daerah (BPKPD) Kabupaten Pamekasan Yang Dimediasi Oleh Profesionalisme - Eko Purnomo; Mei Indrawati; Chamariyah Chamariyah (Universitas 45 Surabaya, 2024)
Eko Purnomo, 2024. The Influence of Organizational Culture and Work Experience on the Performance of Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD) Employees Mediated by Professionalism. Wijaya Putra University Postgraduate Program Surabaya. This type of research uses explanatory research, the research approach uses a quantitative approach. The research sample was 50 respondents. The purpose of this research is 1) To test and analyze whether organizational culture has a direct effect on the performance of employees of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD). 2) To test and analyze whether organizational culture has a direct effect on the professionalism of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD). 3) To test and analyze whether work experience has a direct effect on the professionalism of employees of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD). 4) To test and analyze whether work experience directly influences the performance of Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD) employees. 5) To test and analyze whether professionalism has a direct effect on the performance of employees of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD). 6) To test and analyze whether organizational culture has an indirect effect on the performance of employees of the Regional Financial and Revenue Management Agency (BPKPD) of Pamekasan Regency which is mediated by professionalism. 7) To test and analyze whether organizational work experience has an indirect effect on the performance of employees of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD) mediated by professionalism. The research results show that: 1) Organizational culture has a positive and insignificant effect on the performance of employees of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD) with an original sample value of 0.233. 2) Organizational culture has a significant positive effect on the performance of employees of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD) with an original sample value of 0.427. 3) Work experience has a significant positive effect on the professionalism of employees of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD) with an original sample value of 0.503. 4) Work experience has a positive and insignificant effect on the performance of employees of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD) with an original sample value of 0.182. 5) Professionalism has a significant positive effect on the performance of employees of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD) with an original sample value of 0.564. 6) Organizational culture has a significant positive effect on the performance of employees of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD) which is mediated by professionalism with an original sample value of 0.241. 7) Work experience has a significant positive effect on the performance of employees of the Pamekasan Regency Regional Financial and Revenue Management Agency (BPKPD) which is mediated by professionalism with an original sample value of 0.283.